Pengembangan Rencana Bisnis Untuk Menumbuhkan Jiwa Wirausaha Pelajar Indonesia di Filipina - Witjaksono , Andre Dwijanto; Hartono, Ulil; Sanaji, Sanaji; Artanti, Yessy; Meidiaswati, Harlina; Ramadhan, Muhammad Rizky (Universitas Negeri Surabaya, 2025)
The purpose of this service activity is to improve the understanding of management management, through a business plan development program to foster an entrepreneurial spirit for Indonesian students in the Philippines who are members of the Indonesian Students Association of the Philippines. (PPIF). The activity was carried out based on the results of the initial situation analysis of the FEB UNESA community service team, on financial and other constraints experienced by students and students during further studies in the Philippines. Activities are carried out with the stages of preparation, implementation, ending with monitoring and evaluation. In the preparation stage, training materials were prepared according to the needs of the participants as well as field coordination. PKM activities were carried out on July 6 and 7, 2024 at the Adventist International Institute of Advanced Studies (AIIAS) campus on Aquinaldo Highway, Km. 45.5, Lalaan I, Silang, Cavite 4118, Philippines. The evaluation results showed an increase in participants' understanding of the basic concepts of entrepreneurship, management in general, operations management of businesses, as well as how to find and develop business model canvas ideas by considering financial feasibility through capital budgeting. Participants were very enthusiastic about the training and understood the material provided. Overall, participants were satisfied with the implementation and quality of the training, with an evaluation score of 4.80 on a scale of 1-5. The high value of participant satisfaction was due to the fact that the training was conducted according to schedule in a comfortable atmosphere.